2003
DOI: 10.1124/dmd.31.7.900
|View full text |Cite
|
Sign up to set email alerts
|

Decabromodiphenyl Ether in the Rat: Absorption, Distribution, Metabolism, and Excretion

Abstract: This article is available online at http://dmd.aspetjournals.org ABSTRACT:Among the group of polybrominated diphenyl ethers used as flame-retardants, the fully brominated diphenyl ether, decabromodiphenyl ether (decaBDE), is the most commonly used. Despite the large usage of decaBDE, neither the metabolic pathways nor the absorption have been addressed, and there are very few studies on its toxicology. In this work, it is shown that after a single oral dose of 14 C-labeled decaBDE to rats, at least 10% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
151
2
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(168 citation statements)
references
References 33 publications
13
151
2
2
Order By: Relevance
“…The half-life of tetra-to hexa-PBDEs has been shown to range in mice and rats between 20 and 120 days (Hakk and Letcher, 2003;Geyer et al 2004), with an increase proportional to the degree of bromination. In contrast, BDE-209 appears to be excreted more rapidly (Morck et al 2003;Hakk and Letcher, 2003), though a half-life of 75 days has been reported in another study (Huwe and Smith, 2007).…”
Section: Toxicokinetic Studiesmentioning
confidence: 74%
See 2 more Smart Citations
“…The half-life of tetra-to hexa-PBDEs has been shown to range in mice and rats between 20 and 120 days (Hakk and Letcher, 2003;Geyer et al 2004), with an increase proportional to the degree of bromination. In contrast, BDE-209 appears to be excreted more rapidly (Morck et al 2003;Hakk and Letcher, 2003), though a half-life of 75 days has been reported in another study (Huwe and Smith, 2007).…”
Section: Toxicokinetic Studiesmentioning
confidence: 74%
“…BDE-47, BDE-99, BDE-153) are usually well absorbed following oral exposure (Orn and Klasson-Wehler, 1998;Hakk et al 2002;Staskal et al 2006b). In contrast, absorption of decaBDE is much lower (10% of the dose) (Morck et al 2003). PBDEs distribute to several tissues including the brain, and highest and more persistent concentrations are found in adipose tissue (Hakk and Letcher, 2003), however, this is not the case for BDE-209 (Morck et al 2003).…”
Section: Toxicokinetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two tetra-MeO-BDEs were reported from green turtle and marine mammals from the Southern Hemisphere (Vetter, 2001;Vetter et al, 2002). Moreover, MeO-BDE metabolites containing 6-7 bromine atoms also have been shown in rats exposed to BDE209 (Mörck et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, debromination of BDE209 by juvenile carp following dietary exposure was also observed, and several hexa-through octa-BDE metabolites were found to be more bioavailable than BDE209 itself [24]. In addition to debrominated diphenyl ether metabolites, methoxylated brominated diphenyl ethers (MeO-BDEs) were also regarded as the BDE metabolites in organisms [25][26][27][28]. However, the majority of those studies attributed the MeOBDEs in biota samples to naturally biogenetic processes in marine sponges and algae [29], while very limited studies about MeO-BDEs metabolites of PBDEs were available.…”
Section: Introductionmentioning
confidence: 99%